Numerical Study on Sinusoidal Fluctuated Pulsatile Laminar Flow Through Various Constrictions (Communications in Computational Physics, 2007)
Numerical simulations have been carried out for laminar sinusoidal pulsatingflow in a tube with smooth single constriction. A second-order finite volumemethod has been developed to solve the fluid flow governing equations on a nonstaggerednon-orthogonal grid. The effects of the Reynolds number, the Womersleynumber, the pulsatile amplitude, the constriction ratio and the constriction length onfluid flow in constricted tube will be investigated. It will be demonstrated that thedynamic nature of the pulsating flow greatly depends on the frequency of the flowchanges. It is observed that the peak wall vorticity seems to increase with the increaseof Reynolds number, the pulsating amplitude and the constriction ratio. Thepeak values of instantaneous wall vorticity are not greatly affected by the variation ofWomersly number. The constriction length does not put a significant impact on theflow instantaneous streamline behaviors compared with other parameters. However,the peak wall vorticity increases monotonically with the decrease of the constrictionlength.